2011
DOI: 10.1111/j.1365-2621.2011.02855.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of encapsulation on the viability of probiotic strains exposed to lethal conditions

Abstract: The effect of microencapsulation on the viability of Lactobacillus casei, L. paracasei, L. acidophilus Ki and Bifidobacterium animalis BB-12 during exposure to lethal conditions (25% NaCl, pH 3.0 and 55-60°C) was evaluated. Results demonstrated that survival of probiotic strains to the imposed lethal stress conditions was strain dependent. With the exception of exposure to 25% (w ⁄ v) NaCl, L. acidophilus Ki (free and encapsulated cells) demonstrated the highest survival rates through exposure to lethal condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…The homogenized samples or 1 mL of free cells suspensions was diluted with peptone water to appropriate concentrations and plated onto MRS agar. The plates were incubated anaerobically for 48 h at 37 °C (Borges et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The homogenized samples or 1 mL of free cells suspensions was diluted with peptone water to appropriate concentrations and plated onto MRS agar. The plates were incubated anaerobically for 48 h at 37 °C (Borges et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…They should be present at least 10 6 cfu/g of food product for the therapeutic effect (Annan et al, ). However, it is well known that probiotics are sensitive to several factors such as acidity, pH, time and temperature of storage, and oxygen content (Borges et al, ; Fritzen‐Freire et al, ; Semyonov et al, ). In order to improve the survival of probiotic bacteria, several protection techniques like appropriate selection of acid and bile resistant strains, use of oxygen impermeable containers, two‐step fermentation, stress adaptation, and microencapsulation have been carried out (Kailasapathy & Chin, ; Picot & Locroix, ; Sabikhi, Babu, Thompkinson, & Kapila, ).…”
Section: Introductionmentioning
confidence: 99%
“…Borges et al . () evaluated the viability of L. casei , L. paracasei , L. acidophilus Ki and B. animalis BB‐12 encapsulated in alginate beads through extrusion method during exposure to lethal conditions (25% NaCl, pH 3.0 and 55–60 °C). Results demonstrated that survival of probiotic strains under the imposed lethal stress conditions was strain dependent.…”
Section: Encapsulation Methods For Probioticsmentioning
confidence: 99%
“…2 and 3). This inactivated ''shoulder'' indicates that there might be a thermal death point or the temperature reached the lethal temperature during this period of time (Borges et al, 2012). However, there was just a slight difference between the viable count values of Bb12 after 9 min and 12 min of baking (about 10 2 CFU/g) and the viable counts in the bread baked at the three different temperatures had no significant difference after baking for 6 min.…”
Section: Variation Of Viable Counts In Bread During Bakingmentioning
confidence: 95%